Acoustic impedance-based size-independent isolation of circulating tumour cells from blood using acoustophoresis. Issue 24 (7th November 2018) - Karthick, S.; Pradeep, P. N.; Kanchana, P.; Sen, A. K.
Abstract : Here, we report a label-free method based on acoustic impedance contrast for the isolation of CTCs from peripheral blood mononuclear cells (PBMCs) in a microchannel using acoustophoresis. Applying this method, we demonstrate the label-free isolation of HeLa and MDA-MB-231 cells from PBMCs. Abstract : Label-free isolation of CTCs from blood is critical for the development of diagnostic and prognostic tools for cancer. Here, we report a label-free method based on acoustic impedance contrast for the isolation of CTCs from peripheral blood mononuclear cells (PBMCs) in a microchannel using acoustophoresis. We describe a method in which the acoustophoretic migration of PBMCs is arrested by matching their acoustic impedance with that of the sample medium, and CTCs that have different acoustic impedance compared to PBMCs migrate toward the pressure node or antinode and thus become isolated. We show that acoustic streaming which can adversely affect the CTC isolation is suppressed owing to the inhomogeneous liquid flow configuration. We establish a method for isolation of CTCs that have higher or lower acoustic impedance compared to PBMCs by controlling the acoustic impedance contrast of the liquids across the channel. Applying this method, we demonstrate label-free isolation of HeLa and MDA-MB-231 cells from PBMCs (collected from 2.0 mL of blood) within one hour yielding a recovery of >86% and >50-fold enrichment. Combined impedance and size-based sorting is proposed as a promising tool for the effective isolation of CTCs from blood.